PELATIHAN PEMBUATAN LULUR HERBAL UNTUK MEMBANGUN EKONOMI KREATIF DI KELURAHAN BENDUL MERISI, SURABAYA - Ferdinan, Bernardus Aris; Priskila, Onny; Indrawati, Lilik; Harefa, Mei Kristiani; Nirwan, Klaudiana Cindi (Universitas Sanata Dharma, 2025)
The background of the community service program is to address the community's needs for environmentally friendly, healthy, and chemical-free health products. Skin health for urban communities is a crucial aspect, as living in a city area is often synonymous with exposure to intense sunlight, pollution, dust, and smoke, which can damage skin health. However, it is not uncommon for modern health products to contain chemicals that can damage the skin. Therefore, a healthy, natural, and inexpensive health product is needed. Herbal scrub is a product that meets the demand for natural health products. This community service program was conducted in Bendul Merisi Village, Surabaya, in which the participants were housewives. From this community service program, the participants gained an understanding of herbal scrub products, their benefits, manufacturing processes, ingredients, uses, and economic benefits.